China rise as global power - Singh, S. P. (New Delhi, 2011)
China is striving to develop into a world power despite of questionable foreign policy. China's arms sales and territorial disputes are causing global concerns. Her present is characterized by economic, social, environmental and political problems. This book, therefore, aims at selection of literature for our readers to enable them to examine and analyze legitimacy of its rise as global power. The book also includes authoritative sources on regional challenges, security Threat, India China relations and implications for the future.
Keywords: China and world politics